FACTORS AFFECTING INVESTMENT INTERST IN THE CAPITAL MARKET IN GENERATION Z AND MILENNIALS - Hervianti, Fazalika Alfitri; Musyaffi, Ayatulloh Michael; Hasanah, Nuramalia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study examines how Financial Literacy, Financial Inclusion, and Risk Perception affect investment interest in the capital market among Generation Z and Millennials. It highlights that while these groups are increasingly interested in investing, they face challenges due to low financial literacy and risks of fraud. Using a quantitative survey approach and analyzing data with SmartPLS, the findings reveal a strong influence of the three factors on investment interest. The study builds on the Theory of Planned Behavior (TPB) and suggests further research could investigate additional factors like social influence, macroeconomic conditions, and fintech.